Pesticide residues: Bridging the gap between environmental exposure and chronic disease through omics - Lingling Cao; Qiyuan Kang; Yuan Tian (Ecotoxicology and Environmental Safety)
Pesticide residues, resulting from agricultural practices, pose significant health and environmental risks. This review synthesizes the current understanding of pesticide impacts on the immune system, highlighting their role in chronic diseases such as asthma, diabetes, Parkinson's disease (PD) and cancer. We emphasize the significant role of omics technologies in the study of pesticide toxicity mechanisms. The integration of genomics, proteomics, metabolomics, and epigenomics offers a multidimensional strategy for a comprehensive assessment of pesticide effects, facilitating personalized risk management and policy formulation. We advocate for stringent regulatory policies, public education, and global cooperation to enhance food safety and environmental sustainability. By adopting a unified approach, we aim to mitigate the risks of pesticide residues, ensuring human health and ecological balance are preserved.